2022
DOI: 10.3390/cryst12101409
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on the Deformation Mechanisms in a Ni-Co-Based Superalloys

Abstract: The tensile properties of a Ni-Co-based superalloy were investigated from room temperature to 900 °C. From 25 to 650 °C, the yield strength and tensile strength of the alloy decreased slightly, while the elongation decreased sharply. From 760 °C to 900 °C, the yield strength and tensile strength were greatly reduced, while the elongation also had a low value. With the increase in temperature, the deformation mechanism transformed from anti-phase boundary shearing to stacking fault shearing, and then from defor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Hu et al [60] showed that Ni-Co-based superalloys have very poor ductility, <5% elongation, at temperatures in this temperature range, as shown in Figure 12. The fracture surface gradually changed from ductile to intergranular brittle as the tensile testing temperature increased from room to 750 • C when decohesion took place at the interface between the γ' precipitates and the γ matrix on the fracture surface.…”
Section: Ni and Nickel Alloysmentioning
confidence: 87%
See 3 more Smart Citations
“…Hu et al [60] showed that Ni-Co-based superalloys have very poor ductility, <5% elongation, at temperatures in this temperature range, as shown in Figure 12. The fracture surface gradually changed from ductile to intergranular brittle as the tensile testing temperature increased from room to 750 • C when decohesion took place at the interface between the γ' precipitates and the γ matrix on the fracture surface.…”
Section: Ni and Nickel Alloysmentioning
confidence: 87%
“…However, Ni-based superalloys are prone to high-temperature embrittlement in the intermediate-temperature range 600 to 900 • C unless precautions are taken [58,59]. Ni-based superalloys are used at temperatures of 650-700 • C and sometimes reach as high as 800 • C [60].…”
Section: Ni and Nickel Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…The change in the deformation mechanism is another cause behind the ductility drop at 900 °C. According to several pieces of research [ 61 , 62 , 63 ], once the deformation mechanism changes, the ductility might decrease simultaneously. The size of the γ′ phase and deformation temperature usually affect the deformation mechanism.…”
Section: Discussionmentioning
confidence: 99%